Impact of Soccer Player Migration: Evaluating the Global Soccer Power Dynamics on Skill Drain in Africa - Durodolu, Oluwole; Abubarkar, Folurunsho; Oladokun, Bolaji David; Akintolu, Morakinyo (Indonesian Journal of Sport Management, 2024)
This paper examines the phenomenon of soccer player migration from Africa to other continents, particularly Europe and Asia, and its impact on skill drain in African football. Using data from the 2023 Africa Cup of Nations (AFCON), we analyze the extent and patterns of player migration, factors driving migration, and the implications for African football development and global soccer power dynamics. Our findings reveal a significant outflow of players from Africa to Europe, with economic disparities, better professional opportunities, and infrastructural gaps driving migration. West Africa emerges as the primary source of migrating players, particularly to European clubs. This trend has adverse effects on the development of local football leagues, reducing the quality of domestic competitions and diminishing the popularity of local leagues among football enthusiasts. To address skill drain and promote the sustainable development of soccer talent in Africa, we propose several strategies, including investing in youth development programs, establishing football academies, strengthening domestic leagues, and offering competitive salaries and incentives to players. By implementing these measures, African countries can retain talent locally, strengthen their leagues, and contribute to the growth and success of African football.